Characterization of the Dielectric Barrier Discharge (DBD) Plasma Jet for Staphylococcus Aureus Bacteria Deactivation - Mohammed K. Khalaf (Journal of Global Pharma Technology, 2020)
In this paper, the insulation barrier of the dielectric-barrier discharge (DBD) plasma jet is discharged at atmospheric pressure .Where the degradation efficiency of the DBD plasma jet is evaluated on bacteria of Staphylococcus aureus with different exposure times. The influence of the flow rate and applied voltage of the argon gas used is studied and linked to the temperature and column length of the plasma jet. In addition, the Optical Emission Spectroscopy (OES) is examined to detect plasma parameters such as electron temperature and electron density. OES is also used detect active species within a plasma column such as OI, N2 and OH and other. The percentage of bacteria growth inhibition is increased directly with increased time of exposure from the DBD plasma jet. Keywords: Dielectric barrier discharge, Non-thermal plasma, Bacteria inactivation. Optical Emission Spectroscopy.